Fithrah, Basic Human Potential and the Development of Moderate Character in Religion Thematic Analysis of Hadiths of Fithrah - Nadhiran, Hedhri; Kholifah, Umi Nur; Fajar, M. Patuloh; Afaningtyas, Ananda Arih (Program Studi Tasawuf dan Psikoterapi, 2024)
This article is based on the idea that there are a tendency to understand hadith in a partial way and the demand for its relevance in answering contemporary problems. This is what happens with the concept of fitrah, where the hadiths containing this theme are very diverse, but the analysis of their understanding tends to be carried out separately. Also how this concept can be developed and useful in the Indonesian context, especially regarding religious moderation. To answer this problem, the author conducted library research to examine the meaning of fitrah in the Prophet's hadith by using hadith books, such as Sahih al-Bukhari as the primary data source. After the fitrah hadiths were obtained, they were then analyzed using a thematic-comprehensive method. The results of the research show that there are 2 (two) main meanings contained in the fitrah hadiths, namely: First, the nature of the religious potential of monotheism or the affirmation of God. This potential exists in every creature because it is a gift from God that was given along with the creation of humans. Second, purity. This second meaning is in principle a consequence of the religious potential that exists within humans, both physical and psychological (inner). Fitrah as basic human potential can grow into positive and/or negative characters. Therefore, the effort to maintain it is to carry out actions that support its existence, such as maintaining personal cleanliness, abstaining from disgraceful actions, worshiping according to guidance and praying. Regarding religious moderation, the potential of fitrah can be developed as a basis for forming moderate character in line with efforts to realize the element of 'purity' that accompanies fitrah. For this reason, there are 3 (three) things that must be optimized so that the ideal moderation character in children can be formed, namely: instilling values, presenting role models, and giving orders and prohibitions